2014
DOI: 10.1007/s00520-013-2093-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical and nonclinical characteristics associated with health-related quality of life in patients with high-grade gliomas: a feasibility study

Abstract: Purpose Results from several studies suggest that there is value in evaluating the association between nonclinical characteristics of patients and quality of life (QoL), but few studies have focused on brain cancer. The primary goal of this feasibility study was to explore the relationship between clinical factors and nonclinical factors and QoL in brain cancer patients. Methods Participants in this cross-sectional study were drawn from two hospital sites. Eligible patients were 18–75 years old with a pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…41,45 Education Patients with greater levels of formal education were found to report significantly greater HRQoL in two studies than patients with less education, 40,41 yet no significant difference was present in a further 3 studies. 39,42,44 Greater previous education was also found to relate significantly to reduced distress, 33,41 but not anxiety. 33…”
Section: Marital Statusmentioning
confidence: 88%
See 2 more Smart Citations
“…41,45 Education Patients with greater levels of formal education were found to report significantly greater HRQoL in two studies than patients with less education, 40,41 yet no significant difference was present in a further 3 studies. 39,42,44 Greater previous education was also found to relate significantly to reduced distress, 33,41 but not anxiety. 33…”
Section: Marital Statusmentioning
confidence: 88%
“…No effect of ethnicity was found for anxiety, 33 distress, 14 depression, 33 or HRQoL. 42 Litofsky et al demonstrated a significant role of ethnicity for levels of physician-reported depression, 20 although findings were highly skewed by small numbers of nonwhite participants.…”
Section: Ethnicitymentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have reported that individual and health-related characteristics such as age and time since diagnosis are associated with HQOL in adolescents with cancer (Lee, Han, & Park, 2013; Porter, Menon, & Vick, 2014). However, in this study, those factors showed no significant relationship with the HQOL of adolescents with leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the number of elderly individuals is a recognized social concern, and in recent years, there have been several studies regarding elderly individuals living alone. However, most of these examined quality of life [ 4 6 ], the prognosis of illness or impairment [ 7 ], or gender differences [ 8 , 9 ]. Although aging cannot be prevented, better understanding by local residents can help them feel healthy despite functional deterioration and some diseases.…”
Section: Introductionmentioning
confidence: 99%